ANALISIS STRATEGI MITIGASI BENCANA BANJIR ROB DI PESISIR KABUPATEN KENDAL TERHADAP INDEKS KERENTANAN PESISIR (CVI) TAHUN 2024 - Dhimas Rizkhy Pratama; Pipit Wijayanti; Chatarina Muryani (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
The rise in sea levels due to ice melting in the Antarctic region increases the risk of tidal flooding, particularly in coastal areas with low-lying topography, such as the northern coast of Java. Kendal Regency is one of the regions vulnerable to this disaster. Therefore, this study aims to (1) analyze the level of coastal vulnerability to tidal flooding in Kendal Regency using the Coastal Vulnerability Index (CVI) in 2024 and (2) formulate mitigation strategies to reduce vulnerability to tidal flooding in Kendal Regency in 2024.The CVI assessment in this study is based on several key parameters, including geomorphology, shoreline changes, land elevation, beach slope, sea level rise, average tidal range, and wave height. The sampling technique was conducted using purposive sampling by selecting sub-districts in coastal Kendal that are affected by tidal flooding. Data collection methods included field observations, image interpretation, and documentation. The mitigation strategy formulation method focuses on parameters that significantly contribute to the vulnerability level in each coastal sub-district. The research findings indicate that (1) the coastal areas of Kendal Regency have varying levels of vulnerability, classified as low and moderate. The low vulnerability category is found in Kangkung, Cepiring, and Brangsong sub-districts, while the moderate category includes Rowosari, Patebon, Kendal, and Kaliwungu sub-districts. (2) The mitigation strategies for the coastal areas of Kendal Regency consist of structural and non-structural approaches. Structural mitigation includes beach reclamation, beach restoration, seawall construction, mangrove planting, polder and retention pond development, breakwater construction, and elevation of houses near the coastline. Meanwhile, non-structural mitigation involves public education and awareness programs (educational campaigns and emergency response training), capacity building for local authorities, and the implementation of an early warning system.